E-010 Endovascular coil embolization of unruptured middle cerebral artery aneurysm with incorporated branch. (22nd July 2018) - Jung, Y; Choi, K; Kim, J; Chang, C; Seo, S; Lee, Y
Abstract : Introduction/purpose: Endovascular coiling has emerged as an option in the management of unruptured intracranial aneurysms traditionally being treated by surgical clipping. Unlike aneurysms elsewhere, middle cerebral artery (MCA) aneurysms have several features that are advantageous for surgical procedures. In contrast, endovascular treatment can be somewhat difficult at MCA aneurysms, due to the small parent vessel, difficulty in obtaining the proper working projection, and by incorporating a branch vessel into the aneurysm. As the tendency of endovascular management of aneurysms grows to incorporate MCA aneurysms, we report the results of coil embolization of incorporated MCA aneurysms. Materials and methods: During the last 6 years (2012˜2017), 129 aneurysm were treated by single neurosurgeon, including 10 incorporated MCA aneurysms. The mean neck, height and width of aneurysms were 3.74±1.07, 4.26±1.06 and 3.97±1.03. The mean aspect ratio and dome to neck ration were 1.19±0.37 and 1.09±0.21. Results: All aneurysm treated double microcatheter technique in 9 cases and triple microcathter technique in 1 case without procedural related complications. Post-coiling angiograms showed 4 complete occlusions (40%), 5 remnant neck (50%) and 1 remnant sac (10%). A follow up periods (11.6±6.0 months, 3 to 25 months), no recurrence and bleedings. One patient was suffered small cerebral infarction after one month but without permanent neurological deficits. Conclusion: Our study shows that incorporated aneurysms could be efficiently treated by endovascular coiling with good results. In most cases, single microcathter technique is not possible and more than two more microcatheters are required in complex aneurysms. Incorporated MCA aneurysm could be coil embolization with relative low procedural complication and mid-term durability. And it does not mean that the endovascular coil embolization can solve all MCA aneurysms. However, complex MCA aneurysms are well worth trying endovascular coil embolization and it will develop further and larger series with long-term imaging follow-up are required to confirm these preliminary results. Disclosures: Y. Jung: None. K. Choi: None. J. Kim: None. C. Chang: None. S. Seo: None. Y. Lee: None.